25(OH)D3 stimulates the expression of vitamin D target genes in renal tubular cells when Cyp27b1 is abrogated. Issue 199 (May 2020) - Kikuyama, Takahiro; Susa, Takao; Tamamori-Adachi, Mimi; Iizuka, Masayoshi; Akimoto, Miho; Okinaga, Hiroko; Fujigaki, Yoshihide; Uchida, Shunya; Shibata, Shigeru; Okazaki, Tomoki
Highlights: We generated Cyp27b1 knock out (KO) mDCT cells by using the CRISPR-Cas9 system. Calbindin-D9K and megalin are common targets of 1, 25(OH)2 D3 and 25(OH)D3. Two VDRE sites in the upstream region of the megalin were identified. Abstract: Recently, it was reported that 25(OH)D3 (25D3) has physiological bioactivity in certain tissues derived from Cyp27b1 knockout mice. To investigate the function of 25D3 in the kidney as an informational crossroad of various calciotropic substances, we employed the CRISPR-Cas9 system to knock out Cyp27b1 in the mouse renal distal tubular mDCT cell line. Unlike the previously reported mice in which Cyp27b1 was targeted systemically, Cyp27b1 knockout mDCT cells did not produce any measurable 1α, 25(OH)2 D3 (1, 25D3) after 25D3 administration. As was seen with treatment of Cyp27b1 knockout mDCT cells with ≥10 −8 M of 1, 25D3, the administration of 10 -7 M of 25D3 translocated the vitamin D3 receptor (VDR) into the nucleus and promoted the expression of the representative 1, 25D3-responsive gene Cyp24a1 . The exhaustive target gene profiles of 25D3 were similar to those of 1, 25D3. Subsequently, we confirmed that 25D3 induced the expression of the calcium reabsorption-related gene calbindin-D9K, in a way similar to 1, 25D3. We also found that 1, 25D3 and 25D3 induced the expression of the megalin gene. A chromatin immunoprecipitation assay identified two vitamin D response elements in the upstream region of the megalin gene that seemed to contribute to its expression. Together, we surmise that the ability of 25D3 to stimulate VDR target genes may provide a novel perspective for its role in certain tissues.